Microplastics and human health: a narrative review of current evidence, knowledge gaps, and future research directions - Yanni, Daffa Arkananta Putra (PT. Lentera Kesehatan Indonesia, 2026)
Microplastics (MPs) have become widespread in food, water, air, and various consumer products, raising concerns about their potential impact on human health. Although research on this topic has grown rapidly, existing evidence remains fragmented, and the extent of associated health risks is not well understood. This narrative review aims to synthesize current evidence on human exposure to MPs, their biological mechanisms, and potential health effects, while identifying key knowledge gaps and future research priorities. This narrative review synthesized recent findings from peer-reviewed studies published between 2015 and 2025. Literature was identified through major scientific databases and manual reference checks, focusing on exposure pathways, biological mechanisms, and possible health outcomes related to MPs. Because this review relies solely on previously published data, ethical approval was not required. The literature shows that humans are exposed to MPs primarily through ingestion and inhalation. Experimental studies indicate that MPs can cross epithelial barriers, induce oxidative stress, and provoke inflammatory responses, although human evidence remains limited. Potential health implications include gastrointestinal disturbances, respiratory irritation, and possible reproductive or metabolic effects. However, inconsistent detection methods and limited epidemiological data hinder clear risk assessment. While MPs may pose emerging health risks, substantial knowledge gaps remain. Future research should prioritize standardized analytical methods, realistic exposure assessments, and long-term human studies. Strengthening preventive policies and reducing plastic pollution will be essential to protect public health.